Study of acute phase reactants in children with sepsis, with special reference to C-reactive protein and procalcitonin - Murthy, G R Rajashekara; Pradeep, R; Sanjay, K S; Kumar, Vinay; Sreenivas, S K (Indian Journal of Child Health, 2015)
Background: Several inflammatory markers have failed to meet the requirements for an early diagnosis of sepsis in children. Study results and trends show that measurement of the combination of biochemical markers offers the best prospects for research on early diagnosis of sepsis. Objectives: To evaluate the serum levels of C-reactive protein (CRP) and procalcitonin (PCT) as markers of early sepsis in pediatric patients. Methods: All the hospitalized children aged more than 28 days with clinically suspected sepsis, as per the definition given by International Pediatric Sepsis Consensus Conference, were selected. The patients were divided into two groups; one with culture proven sepsis and the other with culture negative sepsis. CRP and PCT levels were measured at the time of admission and 48 h after admission. Results: A 40 patients were studied, out of that 15 had culture positive and 25 had culture negative sepsis. The mean PCT level was significantly higher at admission than at 48 h after admission, and the mean CRP level was significantly lower at admission than at 48 h after admission indicating PCT as early marker of sepsis. Conclusion: CRP and PCT levels have favorable test performance in differentiating between culture positive and culture negative sepsis. PCT is earlier to rise compared to CRP and PCT is best in predicting the severity followed by CRP.